Application of Geostatistical Tools to Quantify Spatial Variability of Selected Soil Chemical Properties From a Cultivated Tropical Peat - Balasundram, Siva Kumar; Mohd Hanif, Ahmad Husni; Ahmed, Osumanu Haruna (2008)
Abstract : Quantification of spatial variability is a vital prerequisite agriculture.This study was aimed at quantifying the spatial variability of selected chemical properties in a tropical peat cultivated with pineapple. A 1 –ha study plot was established in a commercial pineapple plantation in Simpang Rengam , Johor. Georeferenced topsoil samples ( n = 60 ) were obtained systematically from 8 x 18 m spacings in the x and y direction, respectively.These samples were tested for total C , extractable P , K , Cu , Zn and B.Soil data were first explored using univariate statistics , including normality check , non – spatial outlier detection and data transformation.This was followed by variography and kriging analyses to quantify the spatial variability of chemical properties.Results revealed a high degree of spatial variability in the majority of chemical properties , which exhibited non- normal distributions with CVs ranging from 12 to 54 %.All properties exhibited a definable spatial structure , which were described by either spherical or exponential models.Carbon , P and B showed strong spatial dependence. The majority of properties had a short effective range.Surface maps of chemical properties clearly showed spatial clustering of test values.Expecting K , all other properties showed acceptable accuracy of interpolated values. These combined data suggest the need for a site – specific approach in managing tropical peat cultivated with pineapple , particulary with regard to nutrient management.